TERRORISM IN CONTEMPORARY NIGERIA: A LATENT FUNCTION OF OFFICIAL CORRUPTION AND STATE NEGLECT - Zumve, Samuel; Ingyoroko, Margaret; Akuva, Isaac Iorhen (European Scientific Journal, ESJ, 2013)
The contemporary Nigeria society is engulfed by terrible acts of Terrorism. Be it kidnapping by the Niger Delta Militants or bomb attacks by members of the Boko Haram sect. These acts of terrorism have seriously caused untold hardship to the Nigerian populace. The discourse of the argument put forward in this paper is that contemporary terrorism in Nigeria is a product of prolonged failure of the Nigerian state to show characteristics or fulfill the purposes accepted as normal or beneficial to the totality of her citizens. The paper establishes the relationship between official corruption and terrorism. Using the principles of the Dialectical Materialistic Theoretical Frame, the paper examines several variable factors that can help in the explanations of the relationship between official corruption, state neglect and terrorism in Nigeria. While the paper recognizes that there are both religious and ethnic variables that influence these terrorist acts, official corruption and state neglect of the masses stands out as the most persuasive, compelling primary explanation for terrorism in Nigeria.